IGF-1 regulates cancer cell immune evasion in prostate cancer - Nandakumar, Ashwin M.; Barberis, Alessandro; Kim, Jinseon; Lang, Cameron R.; Mills, Jack V.; Rieunier, Guillaume; Doultsinos, Dimitrios; Taylor, Avigail; Jainarayanan, Ashwin; Phyu, Su M.; Campo, Leticia; Easton, Alistair; et al. (Scientific reports, 2025)
Insulin-like growth factor-1 (IGF-1) is associated with prostate cancer (PCa) development and lethality and exhibits immunosuppressive properties in other models. We investigated IGF-1’s tumor-intrinsic immune effects in PCa to understand mechanisms underlying its poor immunotherapy response. Transcriptional profiling of human (DU145, 22Rv1) and murine (Myc-CaP) PCa cells revealed that IGF-1 suppresses cytokine signalling, antigen processing and presentation, and additional immune regulatory pathways. We further examined the expression of components involved in cancer cell recognition and immune evasion: the antigen processing machinery and PD-L1 checkpoint. IGF-1 downregulated key elements such as transporters associated with antigen processing (TAPs), endoplasmic reticulum aminopeptidase-1 (ERAP-1), and Class I β2-microglobulin, without significantly altering Class I allele expression. These changes were associated with reduced surface presentation of Class I complexes on Myc-CaP cells, suggesting disrupted peptide transport, processing, and/or presentation. In contrast, IGF-1 upregulated the immune checkpoint CD274 (PD-L1) via IGF receptor/AKT/ERK-dependent signalling. Analysis of TCGA Firehose Legacy PCa data showed higher CD274 expression in tumors with elevated IGF1 and IGFBP5. Multiplex immunofluorescence in primary PCa confirmed increased PD-L1 in patients with high serum IGF-1, supporting its role in immune evasion. Overall, these findings reveal a novel IGF-1-driven immunosuppressive mechanism that may underlie PCa’s resistance to immunotherapy.